Türkiye’de tıbbi yardımla üreme tedavisine erişim ve üreme hakları - Mega, Ertunç; Yenerer Çakmut, Özlem; Sert, Gürkan; Ata, Pınar; İlçin Gönenç, Fulya (İstanbul Medipol Üniversitesi, 2021)
Sağlık hakkı bireyin fiziksel, ruhsal, sosyal iyilik hâlinin devamı için sahip olduğu hakları ifade eder ve bireye sağlıklı yaşamının devamı için ve sağlığının bozulması durumunda sağlığını kazandırmak için gerekenlerin yapılmasını talep etme hakkı verir. Sağlık hakkına ve kapsamına uluslararası belgelerde yer verilmiş ve üreme haklarının bu hakkın önemli bir bileşeni olduğu ve sağlık hakkından ayrılamayacağı özellikle belirtilmiştir. Bu kapsamda devletlerin, cinsel hakları ve üreme haklarını tanıyan, koruyan, kullanılmasını sağlayan, kanun çıkartma ve politika geliştirme gibi gerekli önlemleri alma yükümlülükleri bulunmaktadır. Devletlerin yükümlülükleri arasında sayılan pek çok üreme sağlığı hizmetinin yanında, infertilite durumlarında bireylerin üreme sağlığı ile ilgili hizmetlerden ve bu konudaki tıbbi gelişmelerden yararlanmasını sağlama yükümlülükleri de vardır. Bireylerin bu haklardan yararlanması, çocuk sahibi olup olmamaya karar verme haklarının da bir parçasıdır. Sağlık sorunları nedeniyle doğal yollarla çocuk sahibi olamayan bireylerin bilimsel ve teknolojik gelişmeler kapsamında geliştirilen teknikler ile çocuk sahibi olabilme imkânından yararlanabilme hakları vardır. Makalemizde, üreme hakları bağlamında, bireylerin infertilite durumlarında üremeye yardımcı tekniklere erişim hakkı Türk Hukuku çerçevesinde incelenmiştir.

The right to health refers to the rights belonging to individuals that ensure the continuation of their physical, mental, and social well-being, and also gives them the right to demand the necessary action to be taken to meet the requirements for the continuation of a healthy life and/or for the recovery of health in case of dete- rioration. This right and its scope are included in international documents and it has been emphasized that reproductive rights are an important component of this right and that they cannot be separated from the right to health. In this context, states are obligated to take necessary measures, such as enacting laws and develo- ping policies that recognize, protect, and enable the use of sexual and reproductive rights. In addition to myriad reproductive health services, which are considered to be among the obligations of states, they are also obligated to ensure that individu- als benefit from reproductive health services and relevant medical developments in cases of infertility. The enjoyment of these rights by individuals is also part of the- ir right to decide whether to have children.Individuals who cannot have children naturally due to health problems have the right to benefit from the opportunity to do so with the use of techniques developed as part of the scientific and technologi- cal advancements. In our article, in the context of reproductive rights, individuals’ right to access assisted reproductive techniques in cases of infertility is examined within the framework of Turkish Law.
Access to medically assisted reproduction in Turkey and the reproductive rights
Keywords: İnfertilite; Tıbbi Yardımla Üreme; Üreme Hakları; Infertility; Medical Assisted Reproduction; Reproductive Rights